(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
In this article, Ahmad Zaki Walidi’s "Method in History" reveals information about the Kokturks and Islam and the influence of Islamic culture on the cultures and peoples of Central Asia, Asia Minor and the Far East.